2022
DOI: 10.3390/brainsci12111541
|View full text |Cite
|
Sign up to set email alerts
|

MiniQEEG and Neurofeedback in Diagnosis and Treatment of COVID-19-Related Panic Attacks: A Case Report

Abstract: Background: Both the global COVID-19 pandemic situation, as well as the current political situation in Eastern Europe may exacerbate anxiety and contribute to stress-related disorders such as panic disorder. Electroencephalography (EEG)-based neurofeedback provides both assessment of the subject’s brainwave activity as well as the possibility of its therapeutic correction. It is possible that it can be implemented as an auxiliary treatment in panic disorders of different origin. The aim of this feasibility stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Though low beta has historically been associated with positive mental state aspects, such as focused energy (Abhang et al, 2016;Díaz et al, 2019;Tarrant et al, 2018), the musing thought capability of this wavelength can become detrimental if too high a relative power is reached (Apazoglou et al, 2019). For instance, abundant high-amplitude low beta wave activity is related to persistent sympathetic hyperactivity that influences mental stress (Kopańska, 2022). Thus, the relative power of low beta appears to be a factor in the modulation between the self-monitoring and internal focus capabilities of beta and more toxic applications of reflective thought, such as rumination (Apazoglou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though low beta has historically been associated with positive mental state aspects, such as focused energy (Abhang et al, 2016;Díaz et al, 2019;Tarrant et al, 2018), the musing thought capability of this wavelength can become detrimental if too high a relative power is reached (Apazoglou et al, 2019). For instance, abundant high-amplitude low beta wave activity is related to persistent sympathetic hyperactivity that influences mental stress (Kopańska, 2022). Thus, the relative power of low beta appears to be a factor in the modulation between the self-monitoring and internal focus capabilities of beta and more toxic applications of reflective thought, such as rumination (Apazoglou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This type of internally focused thinking is associated with increased low beta and can result in more negative thinking types like rumination (Apazoglou et al, 2019) and anxiety in excess. Some of the most recent research has identified that high-amplitude low beta waves are related to a persistent sympathetic hyperactivity state that influences mental stress (Kopańska et al, 2022). These associations of differing aspects of anxiety with different ranges of Beta frequencies show how the neighboring frequency bands can interact with or be impacted by anxiety levels in distinct manners, and relationships must be assessed across the spectra to understand how anxiety manifests in the qEEG and can therefore be addressed therapeutically.…”
Section: The Search For Consistency In Defining the Beta-anxiety Rela...mentioning
confidence: 99%
“…QEEG involves quantitative analysis of EEG recordings using statistical signal processing [ 13 ]. The use of quantitative electroencephalography instead of the usual EEG allows for an easier analysis of the results due to their better visualization [ 14 ]. It is also worth noting that quantitative electroencephalography is a very sensitive examination and can detect even very small changes in the functioning of the cerebral cortex [ 15 ].…”
Section: Introductionmentioning
confidence: 99%